Does collaborative tree planting between nonprofits and neighborhood groups improve neighborhood community capacity?. (April 2018) - Watkins, Shannon Lea; Vogt, Jess; Mincey, Sarah K.; Fischer, Burnell C.; Bergmann, Rachael A.; Widney, Sarah E.; Westphal, Lynne M.; Sweeney, Sean
Abstract: In the past decade, urban tree canopy cover goals and tree-planting initiatives have proliferated among local governments and nonprofit organizations across the globe. While research has documented many benefits new trees will provide, less has considered whether active participation of city residents in urban forestry activities might also benefit urban neighborhoods. This paper examines nonprofit tree-planting programs in four cities in the Midwestern and Eastern United States to determine whether and to what extent neighborhood participation in a nonprofit tree-planting project might increase ties between residents, social cohesion, and shared trust in that neighborhood. We leveraged a unique dataset of ecological and social information about tree-planting neighborhoods and matched comparison (non-tree planting) neighborhoods (total neighborhoods = 197; total survey respondents = 1551). The evidence for a social effect of nonprofit tree-planting programs is mixed. When asked directly, neighborhood residents reported observing positive changes. Linear regression analysis reveals significantly higher neighborhood ties reported by individuals in planting neighborhoods. However, we find no significant relationship between tree planting and social cohesion or trust. In single-city models, planting's association with neighborhood ties and social cohesion is only significant in one city, and associations with trust are not significant in any city. Models that aggregate responses at the neighborhood level find no significant association of tree planting. Findings suggest that tree planting may increase neighborhood ties, but that increases in social cohesion and/or trust are not guaranteed. Highlights: Nonprofit tree-planting programs can have social benefits, but benefits are not guaranteed. Collaborative tree planting is associated with higher social ties between neighbors. Nonprofits can adjust program structure to maximize social benefits.